PROBLEM OF LATENT MASS UNDER RADIATION OF METEORS - Smirnov, V. A. (Одеські астрономічні публікації, 2017)
The date on absolute spectrophotometry of meteor spectrograms permit to estimate the number of radiating particles for different brightness of meteor. Methods of nonradiation meteor mass estimation are given. Comparison of observed numbers of radiating concentration with know data of artificial cosmic sample will allow to get the coefficients for calculation the nonradiating meteor mass.